2022
DOI: 10.1002/smll.202206531
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Oxygen Evolution Activity of Layered Double‐Hydroxide via Erbium‐Induced Electronic Engineering

Abstract: water-splitting in industrial applications, OER catalysts with a low overpotential, high activity, and long-term stability are urgently needed to be discovered. [7][8][9][10] So far, the state-of-the-art OER electrocatalysts are noble-metal Ir or Ru oxides, [11,12] while some intrinsic drawbacks including high cost, scarcity, and poor stability restrict their large-scale applications. To this end, reducing the use of Ir and Ru-based materials or developing alternatives is attractive and acceptable.The cut-pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 76 publications
(93 reference statements)
0
38
0
Order By: Relevance
“…Owing to the preferred ionic property of the RE-O bond, it is speculated that the construction of the RE-O-TM framework may realize the conservation of TM─O covalency, while electron removal occurs from the higher RE-4f states. Currently, some RE elements such as Ce, [28][29][30] La, [31][32][33] Er, [34][35][36] and Nd [37,38] have been introduced into a number of electrocatalyst systems to enhance OER. However, the catalytic mechanism based on the f-orbital-induced M-O covalency modulation has rarely been studied and the identification of the active sites of RE-TMOs toward OER is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the preferred ionic property of the RE-O bond, it is speculated that the construction of the RE-O-TM framework may realize the conservation of TM─O covalency, while electron removal occurs from the higher RE-4f states. Currently, some RE elements such as Ce, [28][29][30] La, [31][32][33] Er, [34][35][36] and Nd [37,38] have been introduced into a number of electrocatalyst systems to enhance OER. However, the catalytic mechanism based on the f-orbital-induced M-O covalency modulation has rarely been studied and the identification of the active sites of RE-TMOs toward OER is limited.…”
Section: Introductionmentioning
confidence: 99%
“…5d, for the in situ Raman spectra during the OER, the two characteristic peaks of Ni-O vibrations observed at 457 cm −1 and 538 cm −1 when the applied voltage reached 1.48 V indicated that the true active site of the OER should be the corresponding hydroxide. 78 Meanwhile, NiFe-P@NC showed similar trends in electrocatalytic activity towards the HER, which required a low of 153 and 264 mV to reach 100 and 500 mA cm −2 , respectively (Fig. 5e and f ).…”
Section: Resultsmentioning
confidence: 82%
“…S7a †). 67,68 Cell performance tests were conducted at a temperature of 80 °C (55 °C) and a ow rate of 30 wt% (1 M) KOH solution equal to 200 ccm (300 ccm).…”
Section: Water-splitting Cell Performances Of Electrocatalystsmentioning
confidence: 99%